Addition of two large numbers entered from keyboard using Stack and its application in maintaining a Parking Register - Shah, Priyam S; Desai, Shivani D; Kulkarni, Dwisha R (International Journal of Computer Sciences and Engineering, 2025)
This paper shows how to input two numbers using a keyboard component available in Logisim. The addition is performed using a special data structure called “Stack”. We have used the concept of ASCII input. Addition is done in a digit by digit fashion using the ideology of BCD addition. Also, we have applied this logic to design a circuit for maintaining a parking register of a housing society. A special emphasis has been done to allocate parking for the guest members.